PEMILU SERENTAK DI INDONESIA (ANTARA ORIGINAL INTENT DAN IMPLEMENTASI) - Emy Hajar Abra (Bawaslu Provinsi Kepulauan Riau, 2019)
Since the decision of the Constitutional Court (MK) No. 14 / PUU-XI / 2013 was read, the electoral system underwent a historicdemocratic construction, namely the general election held simultaneously to elect the President and Vice President, DPR, DPD,Provincial, Regency / City DPRD in 2019 and so on. The decision was based on the interpretation of the original intent of Article 22E of the 1945 Constitution, in fact was not able to run as well as expected. Various legal, social and political problems are becoming increasingly out of control. In principle, the problems before, during and after the election that occurred have been understood since the Constitutional Court decided on the constitutionality of the presidential threshold. The decision seemed to